Enterprise architecture for global companies in a digital IT era : adaptive integrated digital architecture framework (AIDAF) /: adaptive integrated digital architecture framework (AIDAF). (2019) - Masuda, Yoshimasa; Viswanathan, Murlikrishna
No abstract available